Respuesta :
Reorder the terms: 2n + -5(5 + n) = 8n + 3(1 + -5n) 2n + (5 * -5 + n * -5) = 8n + 3(1 + -5n) 2n + (-25 + -5n) = 8n + 3(1 + -5n) Reorder the terms: -25 + 2n + -5n = 8n + 3(1 + -5n) Combine like terms: 2n + -5n = -3n -25 + -3n = 8n + 3(1 + -5n) -25 + -3n = 8n + (1 * 3 + -5n * 3) -25 + -3n = 8n + (3 + -15n) Reorder the terms: -25 + -3n = 3 + 8n + -15n Combine like terms: 8n + -15n = -7n -25 + -3n = 3 + -7n Solving -25 + -3n = 3 + -7n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '7n' to each side of the equation. -25 + -3n + 7n = 3 + -7n + 7n Combine like terms: -3n + 7n = 4n -25 + 4n = 3 + -7n + 7n Combine like terms: -7n + 7n = 0 -25 + 4n = 3 + 0 -25 + 4n = 3 Add '25' to each side of the equation. -25 + 25 + 4n = 3 + 25 Combine like terms: -25 + 25 = 0 0 + 4n = 3 + 25 4n = 3 + 25 Combine like terms: 3 + 25 = 28 4n = 28 Divide each side by '4'. n = 7 Simplifying n = 7
2n -5n -25 = 8n +3-15n
-3n -25 = -7n + 3
Plus 3 from both sides
-25 = -4n + 3
Subtract 3 from both sides
-28 = -4n
N= 7
Hope this help!
-3n -25 = -7n + 3
Plus 3 from both sides
-25 = -4n + 3
Subtract 3 from both sides
-28 = -4n
N= 7
Hope this help!